A clínica que se vive: reflexões sobre a prática da Psicologia clínica na contemporaneidade - Souza, Carina Cavalcanti de (2007)
The increasing search for the psychological attendance, express in the waiting list in the clinics, clinic-school and in the private clinics, beyond the increase of the choice of psychology as professional career among the pre-college students, allows us to reflect about the place that is occupied by the Psychology, nowadays. The main focus of this study is the clinical Psychology, an area of psychology. The interest in to deepen the reflection regarding of the place that the psychologist and his acting had been assumed in our society, emerged from our own actuation as clinical psychologist. Reflections concerning the suffering of man of our time, accompanying our inquietude while researcher and made us question about the actuation of clinical psychology, nowadays. This research aimed to understand how the clinical psychologists perceive their practice, attempting to get appointments regarding of what is to be clinical psychologist in contemporaneity, more specifically, in the face of the psychic suffering. Based on a phenomenological perspective of research were accomplished semi-structured interviews and a discussion group with clinical psychologists. From the obtained results, we arrived to the following conclusions: a) the most of participants considered the academic formation of the psychologist insufficient and far from social reality; b) the speeches revealed that there is still a relation between the practice of clinical psychologist and the medical model of attendance. Nevertheless, was observed a change in the new psychologists conception of clinic, but is still in development; c) in the most of speeches, we founded consensus about the idea of that the social context which the contemporaneous world lives, had generated new demands of suffering; d) the clinical listening is considered the specificity of the clinical psychologist. We believe that this study had been contributed to fomenting the discussion about the academic formation of clinical psychologist and, the concepts and models of clinic that now base the actuation of the professionals that are inserted on the work market